2010
DOI: 10.1017/s0033291710001820
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual functioning and the long-term course of schizophrenia-spectrum illness

Abstract: These largely negative findings are discussed in the light of strong predictive relationships existing between genetic risk, diagnosis and functional outcomes. The pattern of predictive relationships suggests that overall cognitive functioning may play less of a role in schizophrenia-spectrum pathology than is widely believed, at least among populations with an evident family history of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…15.2% of the FHR offspring in the NYHRP developed schizophrenia-related psychoses, and verbal memory and motor skills were sensitive predictors of disorder (83.3% and 75.0%, respectively), with associated specificities of 71.6% and 73.6% (Erlenmeyer-Kimling, Rock, Roberts, Janal, Kestenbaum, Cornblatt et al, 2000). However, in the Copenhagen HR Cohort, estimated FSIQ was not found to be predictive of schizophrenia or schizophrenia-spectrum disorders (Carter, Parnas, Urfer-Parnas, Watsone & Mednick, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…15.2% of the FHR offspring in the NYHRP developed schizophrenia-related psychoses, and verbal memory and motor skills were sensitive predictors of disorder (83.3% and 75.0%, respectively), with associated specificities of 71.6% and 73.6% (Erlenmeyer-Kimling, Rock, Roberts, Janal, Kestenbaum, Cornblatt et al, 2000). However, in the Copenhagen HR Cohort, estimated FSIQ was not found to be predictive of schizophrenia or schizophrenia-spectrum disorders (Carter, Parnas, Urfer-Parnas, Watsone & Mednick, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…VIQ and PIQ). Interestingly, a longitudinal study of schizophrenia-spectrum patients (Carter et al, 2010) found no significant IQ decline from 15 years old, as assessed by the WISC, to 24 years old as assessed by the WAIS SF comprising of Vocabulary and Block Design. Their finding supports the notion that intellectual structure is not substantially affected by the progress of the disease, at least in terms of the verbalperformance dimensions represented by Vocabulary and Block Design.…”
Section: Intelligence Structure In Patients With Schizophreniamentioning
confidence: 99%
“…Along with it, schizophrenic patients experience disturbances on activities of daily living (ADLs) and instrumental activities of daily living (IADLs). 5,6 Activities of daily living (ADLs) are activities to fulfill physical needs, including grooming, clothing, urinating/defecating, walking, and feeding. 7 Instrumental activities of daily living comprise of more complex activities for independent living, such as managing finances and medication.…”
Section: Introductionmentioning
confidence: 99%